Introduction to the Special Issue “Religious and Spiritual Experiences” - Anne Austad; Hanneke Muthert (Religions, 2021)
William James’s seminal book, The Varieties of Religious Experience (1902/2012), describes the phenomenology and ‘fruits’ (James 2012, p [...]